PENERAPAN UNDERCOVER BUY DALAM PENANGKAPAN PELAKU TINDAK PIDANA PENGEDAR NARKOTIKA DI WILAYAH HUKUM POLRES GIANYAR - I Wayan Primantara Adi, Utama (Fakultas Hukum Universitas Dwijendra, 2026)
Undercover buy or disguised purchase is a narcotics investigation method, where a police officer acts as a buyer in a narcotics sale and purchase transaction, with the intention that the seller or intermediary can be arrested along with the evidence. The implementation of Undercover Buy in the jurisdiction of the Gianyar Police has been implemented several times, and in 2024 out of 54 case disclosures, the police have carried out Undercover Buy 6 times. The basis for implementing Undercover Buy is Article 75 letter j and Article 81 of Law Number 35 of 2009 concerning Narcotics. The purpose of this research is to determine the implementation and obstacles to the implementation of undercover buying in arresting perpetrators of narcotics trafficking crimes in the jurisdiction of the Gianyar Police. This research is an empirical legal research, this research is explorative and descriptive, the data used are primary data and secondary data, in collecting data the author uses document study techniques, interviews and observations, then the data processing and analysis used are qualitative analysis and quantitative analysis. The research conclusion is that the implementation of undercover buy in the arrest of perpetrators of narcotics trafficking crimes in the jurisdiction of the Gianyar Police was carried out in 3 stages, namely initial preparation in the form of completing administration and determining the Operation Target, implementing undercover buy and finally the arrest stage, after being arrested the officer will carry out the investigation process. Obstacles in the implementation of undercover buy are caused by internal factors, namely factors originating from the police in the form of minimal members implementing undercover buy and the ability to implement undercover buy and external factors, namely non-technical factors, namely obstacles in obtaining information from informants.